Tax avoidance and tax disclosure: A study of Brazilian listed companies - Moraes, Gabriela Silva de Castro; Nascimento, Eduardo Mendes; Soares, Sandro Vieira; Prímola, Bernardo Fernandes Lott (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This study analyzes the effect of tax avoidance on corporate transparency in Brazilian listed companies. The research was based on a sample of 256 non-financial companies listed in the Brazilian stock exchange (B3) from 2010 to 2018. A disclosure index was developed considering the BR GAAP (CPC 32), and tax avoidance measures (Effective Tax Rates – ETR, Cash Effective Tax Rate – CashETR, and Book-Tax-Differences – BTD) were used as explanatory variables in a panel. The findings revealed that tax avoidance has a negative influence in corporate transparency and that the industry and commerce sectors, company size, the level of leverage and profitability, have a positive influence in information disclosure.